Genetic analysis of arylsulfatase A (ARSA) in Chinese patients with Parkinson's disease. (24th August 2020) - Ruan, Yang; Zheng, Ran; Lin, Zhi-Hao; Gao, Ting; Xue, Nai-Jia; Cao, Jin; Tian, Jun; Zhang, Bao-Rong; Pu, Jia-Li
Highlights: Arylsulfatase A ( ARSA) p.L300S variant is absent in either sporadic PD patients or healthy controls. ARSA p.N352S is not significant association with PD in our Chinese cohorts. ARSA p.L300S and p.N352S variants may not be common genetic factors for sporadic PD in Chinese Han population. Abstract: Recently, the arylsulfatase A ( ARSA ) variant c.899 T > C (p.L300S) was identified to be segregated with Parkinson's disease (PD) in one family of Japanese descent. And the variant c.1055A > G (p.N352S) of ARSA was reported as a risk reduction factor for PD in a Japanese population. To further investigate the relationship between ARSA and PD, we screened these two loci of the ARSA gene in 407 sporadic PD patients and 471 healthy controls from a Chinese Han population. However, we did not detect the ARSA p.L300S variant in either PD patients or healthy controls. Moreover, in case-control association analysis, the p.N325S variant showed no significant association with PD. Therefore, these results suggested that these ARSA variants may not be common genetic factors for sporadic PD in Chinese Han population.